When will there be good news? : a novel - Atkinson, Kate (Atkinson, Kate. <U+01C2>t Jackson Brodie series, 2008)
Presents a tale involving the unexpected intersection of three lives, including a woman whose life had been shattered thirty years earlier, an ex-detective on a crowded train, and a teenage girl who is called upon to test her preparedness.